Culture of everyday life: to the issue of structure and content logic of the educational discipline. Part II - V. G. Napadysta (Ukrainian Cultural Studies, 2021)
The article discusses the logic of structure and content of the discipline "Culture of Everyday Life", due to the complexity and versatility of the everyday life phenomenon and interdisciplinarity of methodological optics of its research, the variety of theoretical tools, which, in turn, determines the ambiguity of views on the very essence of the everyday life phenomenon and its components. The analysis of educational programs on "Culture of Everyday Life", that are placed among the elements of educational professional and scientific training programs on "Culture Studies" in higher education institutions in Ukraine, demonstrated the wide variability of their content and structure. In the second part of the article, the characteristic features of the everyday life and its oppositional worlds, which helps to delineate the boundaries of the everyday life, as well as its structures and factual and semantic content, are analysed. In particular, the human body and body techniques in the context of everyday practices; house and settlement as an organized and ordered space of everyday life; meals in different modes of gastronomic practices; clothing and its socio-stratification role in everyday life; emotional, regulatory and value foundations of the world of relationships in a family circle. The variability of the semantic content of the "culture of everyday life" concept is considered and the presence of problems in its conceptualization is noted. Based on this, the very name of the discipline "Culture of Everyday Life" is problematized. Emphasis is placed on the appropriateness of its replacement by "Culture Studies on Everyday Life", which would open new opportunities in the structural and thematic content of this discipline and would contribute to the formation of its own specifics in presenting the everyday life phenomenon, focused not on the boundless world of factuality or as a certain normativeness of everyday life, but on a conceptual view of its content and essence, the search for certain patterns in long-term historical durations, the change of which causes profound structural changes in human community as a whole.